Lipodystrophy of Abdominal Pannus: A Severe Complication of Phosphatidyl Choline Injections - Telang, Parag S. (Indian Journal of Plastic Surgery, 2021)
“Injection lipolysis” or “mesotherapy” is done for introducing various substances into deeper layers of the skin with the aim to dissolve subcutaneous fat. However, the safety profile of these chemicals is poorly regulated. Therefore, they may cause side effects or long-term sequelae that can be disastrous for the patient. We present such a case that required surgical management to salvage it and to give an aesthetically acceptable result.
Keywords: injection lipolysis; phosphatidyl choline; side effects of PPC